1977
DOI: 10.1113/jphysiol.1977.sp012105
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit placental clearing‐factor lipase and transfer to the foetus of fatty acids derived from triglycerides injected into the mother.

Abstract: SUMMARY1. Lipase activity was measured in rabbit placental tissue fragments in late pregnancy. The activity in incubated tissue was greater with heparin (69 %), reduced by NaCi (90 %), but not affected by acetone or ether.2. Pregnant rabbits (28-days gestation) were given triglyceride emulsions intravenously and the change in profile of fatty acids in the maternal and umbilical artery and vein plasma free fatty acid (FFA) measured.3. Those fatty acids predominant in the emulsion were higher in concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…However, it is thought that TG per se cannot cross the placenta, it has to be hydrolysed by lipases first, and studies in rabbits [18] and humans [19] have shown that fatty acids from TG infused into the mother are taken up by the placenta and released into the fetal circulation, whilst isotope studies in guinea pigs indicate that more of the fatty acid in the fetal circulation is obtained from maternal TG than NEFA [20]. Thus, it seems likely that the placenta utilises a mixture of TG and circulating NEFA but the relative importance of these sources of fatty acids in human pregnancy is not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is thought that TG per se cannot cross the placenta, it has to be hydrolysed by lipases first, and studies in rabbits [18] and humans [19] have shown that fatty acids from TG infused into the mother are taken up by the placenta and released into the fetal circulation, whilst isotope studies in guinea pigs indicate that more of the fatty acid in the fetal circulation is obtained from maternal TG than NEFA [20]. Thus, it seems likely that the placenta utilises a mixture of TG and circulating NEFA but the relative importance of these sources of fatty acids in human pregnancy is not known.…”
Section: Discussionmentioning
confidence: 99%
“…VLDL-triglycerides are not transferred intact, but are first hydrolysed by an intracellular placental lipoprotein lipase [95,96]. Lipoprotein lipase activity has been demonstrated in the rat, rabbit and human placenta [97,98]. The rate of transfer of the derived fatty acids to the foetal circulation is limited by the rate of triglyceride lipolysis rather than by reesterification [96].…”
Section: Triglyceridesmentioning
confidence: 99%
“…An infusion of triacylglycerol emulsion (Intralipid, an emulsion of soya bean oil rich in C18:2 and C18:l) given i.v. to the pregnant rabbit appeared to be hydrolyzed by the placenta, allowing increased amounts of FFA to cross the placenta (28). Circulating triacylglycerols are bound to very low density lipoproteins and these authors also demonstrated within rabbit placenta the presence of lipoprotein lipase, an enzyme essential for the hydrolysis of circulating triacylglycerols.…”
Section: Discussionmentioning
confidence: 82%
“…(28,29). An infusion of triacylglycerol emulsion (Intralipid, an emulsion of soya bean oil rich in C18:2 and C18:l) given i.v.…”
Section: Discussionmentioning
confidence: 99%